Disruption of the ABA1 encoding zeaxanthin epoxidase caused defective suberin layers in Arabidopsis seed coats - Choi, Jeongho; Kim, Hyojin; Suh, Mi Chung (Frontiers in Plant Science, 2023)
Suberin, a complex polyester deposited in the seed coat outer integument, acts as a hydrophobic barrier to control the movement of water, ions, and gas. However, relatively little is known about the signal transduction involved in suberin layer formation during seed coat development. In this study, the effect of the plant hormone abscisic acid (ABA) on suberin layer formation in seed coats was investigated by characterizing mutations in Arabidopsis related to ABA biosynthesis and signaling. Seed coat permeability to tetrazolium salt was noticeably elevated in aba1-1 and abi1-1 mutants, but not significantly altered in snrk2.2/3/6, abi3-8, abi5-7, and pyr1pyl1pyl2pyl4 quadruple mutants compared with that in the wild-type (WT). ABA1 encodes a zeaxanthin epoxidase that functions in the first step of ABA biosynthesis. aba1-1 and aba1-8 mutant seed coats showed reduced autofluorescence under UV light and increased tetrazolium salt permeability relative to WT levels. ABA1 disruption resulted in decreased total seed coat polyester levels by approximately 3%, with a remarkable reduction in levels of C24:0 ω-hydroxy fatty acids and C24:0 dicarboxylic acids, which are the most abundant aliphatic compounds in seed coat suberin. Consistent with suberin polyester chemical analysis, RT-qPCR analysis showed a significant reduction in transcript levels of KCS17, FAR1, FAR4, FAR5, CYP86A1, CYP86B1, ASFT, GPAT5, LTPG1, LTPG15, ABCG2, ABCG6, ABCG20, ABCG23, MYB9, and MYB107, which are involved in suberin accumulation and regulation in developing aba1-1 and aba1-8 siliques, as compared with WT levels. Together, seed coat suberization is mediated by ABA and partially processed through canonical ABA signaling.